Proposal of Radiation Education Using Naturally Occurring Radioactive Dust in the Air - Yodoshi, Tsutomu; Sakai, Shuhei; Fujino, Hideki (RADIOISOTOPES, 2025)
We propose the novel source for radiation education using natural nuclides containing in the air. After sampling by air cleaner, remarkable radiation count was found at several survey meters in HEPA filter. These counts showed a gradually increase and reached the steady-state after 90 min collection time. Attenuation of radioactivity showed according to the first-order reaction equation and half-life was estimated about 36 min. Moreover, the energy peaks of 214Pb and 214Bi as progenies of 222Rn were detected in the γ-ray spectral analysis using multi-channel analyzer.